In Search of Substitution Material for Traditional Javanese Wooden Houses - Yulianto P. Prihatmaji; Akihisa Kitamori; Kohei Komatsu (Masyarakat Peneliti Kayu Indonesia, 2011)
Many Javanese traditional timber structures have been destroyed by major earthquake. The impact of the disaster demanded a deeper finding on timber materials for repairing and reconstructing. To understand the mechanical property of timber for Javanese timber house, compression test were carried out for radial and tangential direction. Traditional joint construction use mortise and tenon system that stress yield in intersection occurred. Compression property and partial compression property is quite important for traditional joint construction. Especially, the mechanical properties against density of tropical timber were studied. In this paper, authors showed substitute materials for Javanese timber houses from tropical timber. A total of 288 specimens made from six tropical timber species were tested. All of tropical timber specimens showed strong relationship between Young’s modulus (E) and density. There was clear trend that the smaller density indicated the smaller Young’s modulus. Jati, Nangka, Sonokeling, Ketepeng and Acacia had similar increasing mechanical properties, while in the case of specimen Falcata, it mechanical properties were stagnant. The bigger density indicated the bigger Young’s modulus. Acacia and Ketepeng have MOE and density nearby Jati. Both of specimens has also similar tendency of mechanical properties with Jati.